A History of Violence: Photography and Writing as an Experience, Experiment and Insight. Issue 1 (13th October 2020) - Ziegner, Kai
The material presented here in the form of excerpts was taken from the book "A History of Violence" by Kai Ziegner. It represents the artefact of a PhD in artistic research that is soon to be finished at Linz University of Art and Design (UfG) and Zurich University of the Arts (ZHdK). The main focus of my PhD thesis lays on the artistic examination of my own personal experience of violence. Being born and raised in GDR I wanted to investigate the effects of the political turnaround in my home country more profoundly. I have therefore chosen the time frame from 1986 to 2016 and 21 specific events that are related to different acts of violence as the subject matter of my work. The research methodology that I have developed is hybrid – it encompasses archival research, documentary and conceptual photography and experimental writing. Central topics of my research work are guilt, pointless violence, misleading role patterns, dysfunctional father-son relationship, placelessness, disorientation and various entanglements into historic and contemporary Nazism. I travelled to all 21 places to photograph each site on color and b/w medium format film. Later I reviewed these photographs and started to write about it in different textual forms (i.e. short stories, fictive dialogues, aperçus, metareflexive journal). Eventually I transformed all the material into one experimental book. I consider it to be a means of communication and labour, that enables deeper understanding of severe social change. It is a polyvocal composition intended to be used as study material in teaching or as a template for further artistic processing (e.g. screenplay, playbook, piece of music, dance piece etc.). I have shown excerpts from the book at different international events mostly in the form of performative lectures and/or close readings, in which I actively involve the audience.